Implementation of Digital Library Applications at SMK Wira Buana 2 Citayem Bogor - Zein, Afrizal; Farizy, Salman; Fahrudin, Ndin (Doctoral Program of Social Science, Pasundan University, 2024)
Libraries have long been at the heart of the educational environment, playing a vital role in providing the resources necessary for learning and research. However, with the advent of digital technology, traditional libraries have faced new challenges in providing easy and efficient access to educational resources. Therefore, this research aims to investigate the implementation of digital library applications at SMK Wira Buana 2 Citayem as an effort to improve library services and expand access to learning resources for students and teaching staff. This study will describe the process of implementing digital library applications at SMK Wira Buana 2 Citayem, including platform selection, content development, user training, and integration with other supporting systems. The research method used is a combination of literature studies to understand the basic concepts of digital library applications and case studies to analyze ongoing implementation at SMK Wira Buana 2 Citayem. It is hoped that the results of this research will provide a better understanding of the benefits and challenges in implementing digital library applications in secondary education environments. Apart from that, it is hoped that this study will also provide insight for other schools that are considering carrying out digital transformation in their library services.